2021
DOI: 10.1007/s10856-021-06563-1
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency plasma assisted surface modification of Fe3O4 nanoparticles using polyaniline/polypyrrole for bioimaging and magnetic hyperthermia applications

Abstract: Surface modification of superparamagnetic Fe3O4 nanoparticles using polymers (polyaniline/polypyrrole) was done by radio frequency (r.f.) plasma polymerization technique and characterized by XRD, TEM, TG/DTA and VSM. Surface-passivated Fe3O4 nanoparticles with polymers were having spherical/rod-shaped structures with superparamagnetic properties. Broad visible photoluminescence emission bands were observed at 445 and 580 nm for polyaniline-coated Fe3O4 and at 488 nm for polypyrrole-coated Fe3O4. These samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…From the preliminary hyperthermia and cytotoxicity results, it was shown that coated SPIONs have slightly higher saturation magnetisation values and both coatings have a positive effect on the biocompatibility of the SPIONs. 41 Core-shell nanocomposite materials are another "hot topic" for introducing SPIONs to biological fluids. Inorganic compounds such as calcium phosphate, 42 metallic materials such as silver (Ag) and gold (Au), 43 and biocompatible polymers such as PEG can be used in composite structures.…”
Section: Stabilisation In Aqueous Environments and Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…From the preliminary hyperthermia and cytotoxicity results, it was shown that coated SPIONs have slightly higher saturation magnetisation values and both coatings have a positive effect on the biocompatibility of the SPIONs. 41 Core-shell nanocomposite materials are another "hot topic" for introducing SPIONs to biological fluids. Inorganic compounds such as calcium phosphate, 42 metallic materials such as silver (Ag) and gold (Au), 43 and biocompatible polymers such as PEG can be used in composite structures.…”
Section: Stabilisation In Aqueous Environments and Bioavailabilitymentioning
confidence: 99%
“…From the preliminary hyperthermia and cytotoxicity results, it was shown that coated SPIONs have slightly higher saturation magnetisation values and both coatings have a positive effect on the biocompatibility of the SPIONs. 41…”
Section: Recent Delivery and Targeting Technologies For Spionsmentioning
confidence: 99%
“…Magnetization measurements showed that MoS 2 /Fe 3 O 4 possess a saturation 4g). [11] The superparamagnetic properties of MoS 2 /Fe 3 O 4 can effectively prevent the agglomeration of nanosheets after the magnetic field is removed.…”
Section: Resultsmentioning
confidence: 99%
“…HRTEM images (Figure S1b,d , Supporting Information) further revealed the presence of the crystal lattice fringes with a d ‐spacing of 0.250 nm, which can be assigned to the (220) plane of Fe 3 O 4 . [ 11 ] The corresponding AFM images revealed the uniformity of Fe 3 O 4 NPs on the MoS 2 surface (Figure S1f , Supporting Information), and the thickness was increased to 5.0 ± 0.4 nm. Furthermore, X‐ray photoelectron spectroscopy (XPS, Figure S2 , Supporting Information) and X‐ray diffraction (XRD, Figure S3 , Supporting Information) also confirm the successful synthesis of MoS 2 /Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation